Emotional intelligence of lecturers in a centre of foundation studies / Nurhamizah Ishak and Leele Susana Jamian - Ishak, Nurhamizah; Jamian, Leele Susana (Universiti Teknologi MARA, Cawangan Melaka, 2019)
This study investigates the level of emotional intelligence amongst the lecturer in a centre of foundation studies owned by a public university in Selangor. It was found that the sample have high overall emotional intelligence level and also scored high emotional intelligence level in all four dimensions that were measured such as use of emotions, regulation of emotions, self-emotional appraisal and others emotional appraisal. Besides, there were significant differences between emotional intelligence and demographic variables such as age, academic qualifications and departments. As for the implications of this study, it contributes to the corpus of knowledge in the area of emotional intelligence in local context and provides empirical data to assist Ministry of Higher Education in conducting strategic planning to enhance emotional intelligence amongst lecturers in institutions of higher educations (IHE).